Building a small business that Warren Buffett would love - Brownlee, Adam, 1978- (Wiley, 2012)
"The guide to making money the Warren Buffett wayThe book that presents the same fundamentals that Warren Buffet used to turn an initial $105,000 investment into a $40 billion fortune in a way the general reader can apply, Building A Small Business that Warren Buffett Would Love is a succinct, logical, and straightforward guide to financial success. Highlighting one simple message: that Warren Buffett successfully invests in great businesses with strong fundamentals, it argues that these fundamentals can be replicated in a small business to yield outstanding results. Offering a solution for people wanting to start a business to provide additional income in today's uncertain economy, and designed to help entrepreneurs build fundamentally sound, small businesses using Warren Buffett's business investment perspective, the book covers: An overview of Warren Buffett's investment methodology and how it applies to small businesses The details of the Buffett investment criteria--a consumer monopoly, strong earnings, low long term debt, and high ROE with the ability to reinvest earnings--and the application of these fundamentals to both start-up and existing small businesses An approach to building a small business that applies the well respected principles of Warren Buffett, the book presents an exciting new look at the steps to success that have been proven trustworthy by one of the richest men in the world"--